2018
DOI: 10.1111/jgs.15667
|View full text |Cite
|
Sign up to set email alerts
|

Circulating serum level of retinoic acid and hip fractures among postmenopausal women

Abstract: PURPOSE The aim of this study was to evaluate the serum levels of retinoic acid (RA), an active form of vitamin A, in postmenopausal women with hip fractures from Zhengzhou, China. METHODS This was a case‐control study from the Affiliated Hospital of Zhengzhou University. Serum samples were drawn from 375 postmenopausal women who were diagnosed as having hip fracture and 750 matched controls without fracture. Serum RA levels were evaluated as both a continuous variable and a categorical variable in quintiles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The information about age, ethnicities, current tobacco or alcohol use(yes or no), BMI, basic illness (hypertension, diabetes mellitus, cardiovascular disease, neurological disorders, and hyperlipoproteinemia), falls during the last year(yes or no), hip fracture type (cervical or trochanteric), surgical procedure type (arthroplasty or internal fixation) and family history of fragility fractures were obtained. The included patents also were divided into two groups: a hip fracture group and a concomitant fracture of the hip and upper limb fracture group [11]. In addition, total hip bone mineral density (BMD) of the proximal femur was measured using DXA (Hologic QDR2000/QDR4500).…”
Section: Clinical Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The information about age, ethnicities, current tobacco or alcohol use(yes or no), BMI, basic illness (hypertension, diabetes mellitus, cardiovascular disease, neurological disorders, and hyperlipoproteinemia), falls during the last year(yes or no), hip fracture type (cervical or trochanteric), surgical procedure type (arthroplasty or internal fixation) and family history of fragility fractures were obtained. The included patents also were divided into two groups: a hip fracture group and a concomitant fracture of the hip and upper limb fracture group [11]. In addition, total hip bone mineral density (BMD) of the proximal femur was measured using DXA (Hologic QDR2000/QDR4500).…”
Section: Clinical Informationmentioning
confidence: 99%
“…Li et al [11] reported that the rate of lose bone starting in midlife was ranged from 0.3% to 0.5% per year. The gut microbiota can affect bone density, bone remodeling and bone health [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…All- trans -retinoic acid is the most abundant retinoic acid in nature, and its isomers, which include 9- cis -retinoic acid and 13- cis -retinoic acid, are present at markedly lower levels ( Rühl et al, 2018 ). For example, the serum level of 13- cis -retinoic acid was the rage of 1.2–5.39 ng/mL in human ( Li et al, 2019 ; Yang et al, 2020 ). The usage of 13- cis -retinoic acid was approved by the FDA in 1982 for the treatment of severe acne and has been shown to influence cellular differentiation, cell-cycle progression, cell survival, and apoptosis ( Layton, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, excessive Vitamin A intake has been linked to teratogenic effects and an increased risk of birth defects when consumed at high levels (over 10,000 IU/d) during pregnancy ( Hunt, 1996 ). It can also negatively impact bone quality and increase fracture risks, such as retinoic acid can inhibit osteoblast activity, stimulate osteoclast formation, induce bone resorption, and negatively impact bone quality ( Li et al, 2019 ). A single or short-term dose of approximately 50,000 IU can provoke toxic conditions such as vomiting, increased cerebrospinal fluid pressure, blurred vision, and impaired muscle coordination ( Bendich and Langseth, 1989 ).…”
Section: Impact Of Nutrients On the Ocular Surface And Potential Risksmentioning
confidence: 99%